Kontribusi Sekolah Rakyat Paguyuban Pengajar Pinggir Sungai (P3S) dalam Pendidikan Seks bagi Kelompok Rentan di Yogyakarta: : Studi di Sekolah Rakyat Paguyuban Pengajar Pinggir Sungai (P3S). - Wafidhi, Arif; Rof’ah, Rof’ah (Pekerjaan Sosial, 2024)
The implementation of sex education as sexual harrasment mitigation in Indonesia is still segmented, exclusive, and minor. This condition happened because sex education in Indonesia is still not inclusive as the impact of taboo barrier of social construct existing. This research then explores how sex education is being developed to vulnerability groups by Sekolah Rakyat P3S as social worker on beside Code River. Non-participatory observation and indepth interview were implemented to collect data and P3S as case study approach. The result shows that P3S formualted sex education curriculum concept based on the highest trend of sex knowledge of the students. It emerged two central materials, those are biologist aspect and social protection. Biologist aspect was delivered at the first learning and the other was delivered at the last learning. There were some obstacles in developing sex education at P3S such as students’ loss of concentration and language restriction. Recomendations were made on how to optimalize sex education in vulnerability groups at P3S.